Policies and obligation of women athletes clothing at international sports events: A literature study - Agustina, Dina; Rismayanthi, Cerika; Sumaryanti, Sumaryanti; Yuniana, Rina; Nugroho, Sigit; Haidar, Muhammad Daffa; Wang, Ziyu; Murgolo, Michael (Tanjungpura Journal of Coaching Research, 2024)
Background and Study Aim. The participation of female athletes in a sporting event in each country is very minimal compared to men, basically the State policy has not fully allowed female athletes to wear the hijab. Hijab is familiar to Muslim women but on the other hand the policies of their respective countries do not support Muslim women participating in a sporting event by wearing hijab. This study aims to explore the involvement of Muslim women who wear hijab in international sporting eventsMaterial and Methods. This research used Harzing Publish or Perish to start the search, Scopus database was used, which is considered as one of the best citation indexing tools. The criteria used the PRISMA protocol (preferred reporting items for systematic reviews and meta-analyses). The keywords of this research are ("Muslimah" AND "Sportswear" AND "Women's Participation" OR "Women in Sports"). Based on these results, only 7 journal articles were used in the systematic literature review in this study.Results. The result of this study is that the gradual increase in the number of female Olympians obscures the reality that a woman's opportunity to participate and compete in sports. It can be seen that in several countries there has been an increase in the number of Muslim female athletes participating in championships in the international arena, but the policies given have not allowed female athletes in all sports to cover the aurat or wear the hijab, the obligation of a Muslim is to cover the aurat, which in principle between policies and obligations become two things that intersect.Conclusion. In conclusion, despite a noticeable increase in the number of Muslim female athletes participating in international championships, policy limitations still prevent female athletes in some sports from covering their aurat or wearing the jilbab.